Efficiency Breakthrough of Fluorescence OLEDs by the Strategic Management of "Hot Excitons" at Highly Lying Excitation Triplet Energy Levels. (2nd September 2021) - Lin, Chengwei; Han, Pengbo; Xiao, Shu; Qu, Fenlan; Yao, Jingwen; Qiao, Xianfeng; Yang, Dezhi; Dai, Yanfeng; Sun, Qian; Hu, Dehua; Qin, Anjun; Ma, Yuguang; et al.
Abstract: Aggregation‐induced emission (AIE) and hybridized local and charge‐transfer (HLCT) materials are two kinds of promising electroluminescence systems for the fabrication of high‐efficiency organic light‐emitting diodes (OLEDs) by harnessing "hot excitons" at the high‐lying triplet exciton states (T n, n  ≥ 2). Nonetheless, the efficiency of the resulting OLEDs did not meet expectations due to the possible loss of T n →T n −1 . Herein, experimental results and theoretical calculations demonstrate the "hot exciton" process between the high‐lying triplet state T3 and the lowest excited singlet state S1 in an AIE material 4⁗‐(diphenylamino)‐2″, 5″‐diphenyl‐[1, 1″:4′, 1″:4″, 1′″:4′″, 1⁗‐quinquephenyl]‐4‐carbonitrile (TPB‐PAPC) and it is found that the Förster resonance energy transfer (FRET) between two molecules can facilitate the "hot exciton" process and inhibit the T3 →T2 loss by doping a blue fluorescent emitter in TPB‐PAPC. Finally, the doped TPB‐PAPC blue OLEDs achieve a maximum external quantum efficiency (EQEmax ) of 9.0% with a small efficiency roll‐off. Furthermore, doping the blue fluorescent emitter in a HLCT material 2‐(4‐(10‐(3‐(9 H ‐carbazol‐9‐yl)phenyl)anthracen‐9‐yl)phenyl)‐1‐phenyl‐1 H ‐phenanthro[9, 10‐ d ] imidazole (PAC) is used as the emission layer, and the resulting blue OLEDs exhibit an EQEmax of 17.4%, realizing the efficiency breakthrough of blue fluorescence OLEDs. This work establishes a physical insight in the design of high‐performance "hot exciton" molecules and the fabrication of high‐performance blue fluorescence OLEDs. Abstract : The Förster resonance energy transfer between two molecules can facilitate the high‐lying reverse intersystem crossing process in aggregation‐induced emission and hybridized local and charge‐transfer hosts, thereby reducing the loss from T n to T n −1 state and improving exciton utilization, and finally realizing the efficiency breakthrough of blue fluorescence organic light‐emitting diodes.